The Influence of Vocabulary Mastery Ability to Write Exposition Text of Eighth Grade Students of SMP Negeri 1 Satu Atap Tampahan: The Influence of Vocabulary Mastery Ability to Write Exposition Text of Eighth Grade Students of SMP Negeri 1 Satu Atap Tampahan - Erlinawati Situmorang (Jurnal Mantik, 2020)
This study aims to determine whether there is a relationship between the mastery of vocabulary and the ability to write exposition text for eighth grade students of SMP N l atap tampahan in Academic Year 2019/2020. This research is a correlational study using a quantitative approach. The population consists 112 students, and a sample of 24 students. Based on data processing, the average value (m) of vocabulary mastery by eighth grade students of SMP Negeri 1 atap is 78.12 in the good category, while the average value (m) of the ability to write text the exposition is 81.4 in the very good category. Based on the results of the study, it is known that the calculated value is 0.858 while the r table is 0.404 that significance level of 5%. The value of r (count) is greater than r (table) which is 0.858> 0.404. Thus there is a positive and significant relationship between the mastery of vocabulary to write exposition text for eighth grade students of SMP Negeri 1 atap tampahan in academic year 2019/2020 . Then Ha is accepted and Ho is rejected at a significant level of 5%.